Oral ID® as an adjunctive tool for surgical margin assessment in patients with oral squamous cell carcinoma: a comparative study: Oral ID® as an Adjunctive Tool for Surgical Margin Assessment - Alhajj, Mohammed; Mohammed, Sawsan; Sulaiman, Ahmed (Brazilian Dental Science, 2021)
Objective: The condition of the resected margin in oral squamous cell carcinoma continues to be an important prognostic factor; the use of optic technology could help surgeons in determining the margin status at real time. This study aims to evaluate Oral ID, a hand held device that uses the principal of auto-fluorescence to determine surgical safe margins in patients with oral squamous cell carcinoma, and to compare the results with those of the conventional 1 cm margin method. Material and Methods: This study was a descriptive, comparative analytical study carried out at Khartoum Dental Teaching Hospital and Oral Histopathology Diagnostic Laboratory, Faculty of Dentistry, University of Khartoum. A total of 92 margins obtained from 31 patients, 46 margins were taken by Oral ID and the other 46 were taken by the traditional 1cm method. All margins were examined histologically with conventional Hematoxylin and Eosin stain. Results: It was found that all tumors showed fluorescence loss; A significant association was found between the use of Oral ID and obtaining a free margin P (0.02) the sensitivity of Oral ID was found to be 74% the specificity was found to be 89%. Ten out of the 46 margins obtained by fluorescence showed mild dysplasia and two margins showed high grade dysplasia. The 46 margins obtained by the traditional 1cm margin showed different field alterations two were involved, one was close, five showed high grade dysplasia and 14 showed mild dysplasia yielding a specificity of 52.2%. Conclusion: Using Oral ID for surgical margin assessment increases the accuracy to 74% compared to the conventional method which was found to be 52.2%. The results of the device are comparable to other auto-fluorescence devices of different trademarks. Further development of the device to help overcome its limitations is strongly advised. KEYWORDS Oral ID; Auto-fluorescence; Cancer; Diagnosis; Oral squamous cell carcinoma.